Penerapan Yurisdiksi Universal Terhadap Pelaku Tindak Pidana Foreign Terrorist Fighter - Yogie Indra Kurniawan; Ramlani Lina Sinaulan; Md. Shodiq (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The boundaries of a country's sovereignty today are increasingly blurred due to globalization. The era of globalization is marked by technological advances and free trade between countries. In addition to the positive impact of globalization, globalization also has excesses of crime that are rapidly increasing along with advances in information technology and transformation. Transnational crime has grown to become a threat to society as a result of the globalization era. One of the transnational crimes in the era of globalization is terrorism. In general, terrorism is included in the characteristics of these serious crimes. This is because the criminal act of terrorism is a crime committed using violence or the threat of violence in a deliberate, systematic and planned manner, which creates an atmosphere of terror or widespread fear by targeting state officials, random or unselected civilians, as well as vital objects that are strategic, environmental, and public facilities or international facilities and tend to grow into symmetrical hazards that endanger state security and sovereignty, territorial integrity, peace, human welfare and security, both nationally, regionally and internationally.Keywords: Universal Jurisdiction; Criminal Acts; Foreign Terrorist Fighter AbstrakBatas-batas kedaulatan suatu negara dewasa ini semakin kabur dikarenakan dari globalisasi. Era globalisasi ditandai dengan kemajuan teknologi dan perdagangan bebas antar negara. Selain dampak positif dari globalisasi tersebut, globalisasi juga memiliki ekses kejahatan semakin pesat seiring dengan kemajuan di bidang teknologi informasi dan transformasi. Kejahatan lintas negara telah tumbuh menjadi salah satu ancaman bagi masyarakat sebagai dampak dari era globalisasi. Salah satu kejahatan lintas negara di era globalisasi adalah terorisme. Secara umum terorisme masuk dalam karateristik kejahatan serius tersebut, hal ini dikarenakan tindak pidana terorisme merupakan kejahatan yang dilakukan dengan menggunakan kekerasan atau ancaman kekerasan dengan sengaja, sistematis, dan terencana, yang menimbulkan suasana teror atau rasa takut secara meluas dengan target aparat negara, penduduk sipil secara acak atau tidak terseleksi, serta objek vital yang strategis, lingkungan hidup, dan fasilitas publik atau fasilitas internasional dan cenderung tumbuh menjadi bahaya simetrik yang membahayakan keamanan dan kedaulatan negara, integritas teritorial, perdamaian, kesejahteraan dan keamanan manusia, baik nasional, regional, maupun internasional.Kata Kunci: Yuridiksi Universal; Pelaku Tindak Pidana; Foreign Terrorist Fighter